PUBLIC ADMINISTRATION UNDER MILITARY THREATS: UKRAINIAN EXPERIENCE OF ADAPTING TO CRISIS SITUATIONS - Varenia, Nataliia (Public Management and Policy, 2024)
The article examines the Ukrainian experience of public administration under conditions of military threat as of 2022-2024. The key challenges faced by Ukraine during the full-scale war are analyzed, including the destruction of critical infrastructure and the need to ensure uninterrupted provision of public services. Special attention is paid to the digitization of public administration, which played a decisive role in maintaining the stability of state institutions. The role of the «Action» platform and other innovative solutions that enabled interaction between citizens and the government in crisis conditions is described. The impact of decentralization on the ability of local authorities to respond to the challenges of war has been studied. The interaction with international partners within the framework of the SIGMA program, which is aimed at providing support in the reform of public administration with a course towards European integration, is characterized. A comparative analysis of the Ukrainian experience with other European countries that faced large-scale crises was carried out, and unique aspects of the Ukrainian model of adaptation were revealed. The article analyzes strategies for the restoration and modernization of the state administration of Ukraine in crisis conditions. Attention is focused on the interaction between the state and corporate sectors to maintain economic activity even in conditions of active hostilities. The role of business relocation to safer regions and the influence of state support on the stabilization of the labor market and the economy are outlined. Programs aimed at restoring infrastructure and vital services in cooperation with international partners are mentioned. The experience of implementing temporary solutions to ensure the basic needs of the population is described. It examines the impact of international aid and financial support through IMF and World Bank programs that helped maintain budget stability and avoid economic collapse. The perspectives of public administration during Ukraine's integration into European structures and further strengthening of public administration are highlighted. Special attention is paid to the prospects for the development of public administration in the post-war period, the solution of socio-economic problems, the restoration of infrastructure and the attraction of investments. Strategic directions for reforming public administration for the future are proposed, taking into account the experience of the war and cooperation with international institutions.